UJI EFEKTIVITAS SEDIAAN GEL EKSTRAK BIJI KELENGKENG (Dimocarpus longan Lour.) SEBAGAI OBAT LUKA BAKAR TERHADAP MENCIT PUTIH JANTAN (Mus musculus) - Sitorus, Elly; Thaib, Cut Masyithah; Suryani, Monica; Sarumaha, Vivid Angelina (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Longan seeds contain corrilagin, gallic acid, and ellagic acid compounds which have the potential as an alternative medicine for burns. This study aims to determine the effectiveness of the longan seed extract gel preparation with 3 variations of extract concentration (5%, 7.5%, and 10%) as a burning medicine against white male mice. Longan seed extract was obtained by using the maceration extraction method